Effectiveness of Ventral Dartos Flap as the second layer in Distal and Mid-Penile Hypospadias Repair. - Khan, Shariq Anis; Farhan, Muhammad; Effendi, Fouzia Naeem; Khalid, Salman El; Sharief, Imran; Awan, Adnan Siddiq; Haseeb, Shakeel (International Journal of Endorsing Health Science Research, 2021)
Background: Various methods have been used to reconstruct mid-penile hypospadias; still, massive failure rates and leading complications have been indicated. The present study observes the effectiveness of a technique using a well-vascularized dartos flap as a second layer in distal and mid- penile hypospadias repair. Methodology: This is a cross-sectional study conducted between 2017-2019. A total of 110 male children with hypospadias were operated on. The children with mid-penile or slightly more proximal hypospadias, with or without ventral chordae and with the intact prepuce, were included in the study. Outcome measures comprised of surgical results with the absence of any serious side effects, decent flow, meat stenosis, fistula and dehiscence of glans. Results: The median follow-up duration was 12 months. There were 72 cases of mid penile hypospadias (66.7%), and in 36 cases (33.3%), the meatus was slightly more dorsal. The age of the patients ranged from 1.1 to 11 years, with a mean age of 3.52 ± 2.74 years. Surgery was successful in 105 (95.5%) cases. Four patients presented with meatal stenosis and one with meatal stenosis plus fistula, more than 2 months after surgery. Meatal stenosis was managed by meatoplasty, and in the case of a urethral fistula, the patient was re-operated after at least 6 months. Conclusion: Ventral dartos flap is a safe, effective method with less adverse effect and less time-consuming in patients with distal and mid-penile hypospadias.